2011
DOI: 10.1016/j.juro.2011.05.088
|View full text |Cite
|
Sign up to set email alerts
|

Presacral and Retroperitoneal Lymph Node Involvement in Urothelial Bladder Cancer: Results of a Prospective Mapping Study

Abstract: A substantial proportion of patients have lymph node positive disease in the presacral and retroperitoneal regions, including some with isolated and/or solitary lymph node involvement. While the limited positive lymph node burden in these templates suggests a potential therapeutic role for extending the anatomical boundaries of lymph node dissection, patient survival was poor. Extended lymph node dissection provides important staging information but to our knowledge the therapeutic benefit has yet to be defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Particularly in the primary cases, accurate assessment of LN metastasis helped to determine the application of neoadjuvant chemotherapy or the indication and extent of LND. Although the survival benefits of neoadjuvant chemotherapy and regional LND have been established in muscle-invasive bladder cancer [27,28,29,30], their benefits for UTUC are still controversial subjects. Neoadjuvant chemotherapy may play an important role in the treatment strategy for UTUC because urothelial carcinoma of the bladder and UTUC share some significant characteristics [3,4,5,6,7,8,10]; however, few reports have examined its clinical benefit in UTUC [9], and the indication of neoadjuvant chemotherapy has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the primary cases, accurate assessment of LN metastasis helped to determine the application of neoadjuvant chemotherapy or the indication and extent of LND. Although the survival benefits of neoadjuvant chemotherapy and regional LND have been established in muscle-invasive bladder cancer [27,28,29,30], their benefits for UTUC are still controversial subjects. Neoadjuvant chemotherapy may play an important role in the treatment strategy for UTUC because urothelial carcinoma of the bladder and UTUC share some significant characteristics [3,4,5,6,7,8,10]; however, few reports have examined its clinical benefit in UTUC [9], and the indication of neoadjuvant chemotherapy has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Yüksek riskli ve komorbiditesi olan hastalarda operasyon süresinin uzamasından kaçınılmalıdır ve bu hastalar genişle-tilmiş LN diseksiyonu için uygun olmayabilmektedirler. Genişle- [23]. Bizim serimizde nihai patolojik incelemede pT0 saptanan 24 hastanın 2 sinde LN tutulumu saptandı ve hastaların birisinde neoadjuvan KT öyküsü vardı.…”
Section: Discussionunclassified
“…4,8,10 However, 2 recent studies have reported isolated level III metastases in 3 of 52 (6%) and 1 of 151 (0.7%) patients with node positive disease. 5,6 While this finding may be explained by missing lower level positive nodes on pathological evaluation, it suggests that level III skip lesions may rarely occur.…”
Section: Patterns Of Nodal Spreadmentioning
confidence: 96%
“…4 Miocinovic et al recently described node positive rates of 31% (level I), 18% (level II) and 13% (level III). 5 Combined data from University of Southern California and Oregon Health & Science University indicate nodal metastases in 22% (level I), 9% (level II) and 7% (level III) of cystectomy cases, the latter constituting 28% of those with node positive disease. 6 Multiple other mapping studies have reported rates of nodal metastases that generally fall within these ranges.…”
Section: Patterns Of Nodal Spreadmentioning
confidence: 99%
See 1 more Smart Citation